2018
DOI: 10.1111/jvh.13015
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mutation within an emerging endemic lineage of HEV‐3a

Abstract: Summary The hepatitis E virus can cause chronic infections in immuno‐suppressed patients, and cases have been on the rise globally. Viral mutations during such infections are difficult to characterize. We deep‐sequenced viral populations from 15 immunocompromised patients with chronic HEV to identify the viral lineage and describe viral mutational hotspots within and across patients. A total of 21 viral RNA samples were collected between 2012 and 2017 from a single hospital in Singapore. Sequences covering a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Phylogenetic analyses of concatenated ORF1 and ORF2 sequences from 59 HEV samples revealed that most of the strains belong to genotype 3a (44/59, 75%; shaded, Figure a). When compared with selected strains previously reported in Singapore, our genotype 3a strains clustered closely with four (KT447526, KT447528, AHB282, AHB300) but not with another strain (AH284) that was believed to have been imported (Zhu et al, ) (Figure a). Notably, only one of the genotype 3a strains was from a non‐resident, and the other 43 samples were from Singapore residents.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Phylogenetic analyses of concatenated ORF1 and ORF2 sequences from 59 HEV samples revealed that most of the strains belong to genotype 3a (44/59, 75%; shaded, Figure a). When compared with selected strains previously reported in Singapore, our genotype 3a strains clustered closely with four (KT447526, KT447528, AHB282, AHB300) but not with another strain (AH284) that was believed to have been imported (Zhu et al, ) (Figure a). Notably, only one of the genotype 3a strains was from a non‐resident, and the other 43 samples were from Singapore residents.…”
Section: Resultsmentioning
confidence: 55%
“…Molecular analyses of sequences in our study of human sera revealed genotype 3 to be distinctly the most prevalent (121/143, 84.6%), with genotype 3a as the main circulating strain. Although Teo et al () and Zhu et al () have previously described the identification of genotype 3a in Singapore, the number of their cases (3 and 15, respectively) was small. Our study detected genotype 3a in 44 of 59 patient samples with concatenated ORF1 and ORF2 sequences (74.6%).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations